Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1097/cad.0b013e32832e89c7
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic study on a human osteosarcoma cell line Saos-2 treated with diallyl trisulfide

Abstract: Garlic is generally used as a therapeutic reagent against various diseases, and numerous studies have indicated that garlic and its derivatives can reduce the risk of various types of human cancer. Diallyl trisulfide (DATS), a major member of garlic derivatives, could inhibit the cell proliferation by triggering either cell cycle arrest or apoptosis in a variety of cancer cell lines as shown in many studies. However, whether DATS has the same effect on human osteosarcoma cells remains unknown. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Two proteomic investigations provide additional support to this evidence by showing that organosulfide-sensitive proteins are tightly associated with apoptotic pathways [32,33]. The available data demonstrate how modulation of Bcl-2 family, activation of stress signaling cascades, activation of p53, generation of reactive oxygen species (ROS), changes in calcium homeostasis, and microtubule depolymerization are all implicated in the apoptotic response of cancer cells to Allium sulfur compounds (Fig.…”
Section: Induction Of Apoptosis In Malignant Cellsmentioning
confidence: 79%
“…Two proteomic investigations provide additional support to this evidence by showing that organosulfide-sensitive proteins are tightly associated with apoptotic pathways [32,33]. The available data demonstrate how modulation of Bcl-2 family, activation of stress signaling cascades, activation of p53, generation of reactive oxygen species (ROS), changes in calcium homeostasis, and microtubule depolymerization are all implicated in the apoptotic response of cancer cells to Allium sulfur compounds (Fig.…”
Section: Induction Of Apoptosis In Malignant Cellsmentioning
confidence: 79%
“…Previous research includes efforts to unravel OS development, to study mechanisms of drug response, to identify new biomarkers for prognosis and therapy response, and, to identify putative therapeutic candidates for OS by studying differences within the entire proteome of OS cells or cell lines compared with human osteoblasts (Guo et al , 2007a; Folio et al , 2009; Liu et al , 2009; Zhang et al , 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Cell surface molecules are known to be involved in important biological processes, including proliferation, differentiation, migration and survival (Stevens and Arkin, 2000; Wu and Yates, III, 2003; Scheurer et al , 2005; Lund et al , 2009; Zhang et al , 2009). Also, surface molecules such as growth factor receptors, cytokines, metalloproteases and integrins are implicated in the development and progression of malignancies, including OS (Khanna et al , 2004; Krishnan et al , 2005; Kansara and Thomas, 2007; Guo et al , 2008; Kim et al , 2008; Wan et al , 2009; Rubin et al , 2010).…”
mentioning
confidence: 99%
“…Garlic oils contain major organosulfur compounds, including diallyl sulfide (DAS; 112 g/g), diallyl disulfide (DADS; 1,183 g/g), and diallyl trisulfide (DATS; 751 g/g), and minor amounts of many other volatile compounds (49). These compounds possess potent anticancer, antioxidant, and anti-inflammatory immune modulation activities and antimicrobial properties (2,30,71,72,79,83). The inhibitory effect of DASs against Bacillus cereus, Salmonella sp., and Vibrio cholerae (7,62,63), Staphylococcus aureus and Candida albicans (42,51), Helicobacter pylori (52,58), and Klebsiella pneu-moniae and Pseudomonas aeruginosa (17,37,53,73) were studied, and a recent report has shown that DASs were synergistically effective when combined with antibiotics against antibiotic-resistant strains of Escherichia coli, Enterobacter cloacae, E. faecalis, and Citrobacter freundii (80).…”
mentioning
confidence: 99%